Modern Approach to Formation of the Banking Sector Development Trajectory - Diatlova, Yu. (Економічний вісник Донбасу, 2020)
The results of the study topical issue on effective development of the banking sector with an emphasis on banks with domestic capital are summarized in the article; the modern approach to formatting the trajectory of such development is substantiated.
The factors influencing the development of the banking sector are systematized. External and internal factors are distinguished. The supranational and national levels are defined for the group of external factors. Supranational factors are related to globalization and integration. First of all, these are crisis phenomena in the world economy and financial system, the liberalization of capital movements. External factors at the national level mostly have a negative impact on the development of the banking sector. It is shown that certain external factors of the national level depend on supranational ones, and internal factors depend on national ones.
Internal factors are grouped into those that have a positive and negative impact on the development of the banking sector. The characteristic of the most significant factors is given, their mutual influence is shown. Factors such as the dangerous level of competitive internalization due to the presence of foreign banks in the Ukrainian banking market, the high level of loans and deposits dollarization, low quality of assets and loans have a negative impact on the development of the banking sector. The influence of internal factors on the development of the banking sector is determined. It is proved using dynamic (simulation) modeling based on an impulse process that the development of the banking sector is significantly influenced by the factor of dangerous level of competitive internalization. It is established that such stabilizing factors as the growth of demand for banking services, increasing confidence in the banking system and stabilization of the national currency together compensate for the destabilizing effect of any negative factor, including competitive internalization. The formation of positive internal factors will contribute to the progressive trajectory of the banking sector development, in particular banks with domestic capital. У статті узагальнено результати дослідження актуального питання щодо ефективного розвитку банківського сектору з акцентом на банки з вітчизняним капіталом, обґрунтовано сучасний підхід до формування траєкторії такого розвитку.
Систематизовано чинники, що впливають на розвиток банківського сектору. Чинники розподілені на зовнішні і внутрішні. Серед зовнішніх чинників виокремлено наднаціональний і національний рівні. Чинники наднаціонального рівня пов’язані з глобалізацією та інтеграцією. Перш за все, це кризисні явища в світовій економіці та фінансовій системі, лібералізація руху капіталів. Зовнішні чинники на національному рівні здебільшого негативно впливають на розвиток банківського сектору. Показано, що певні зовнішні чинники національного рівня є залежними від наднаціональних, а внутрішні – від національних.
Внутрішні чинники згруповано на такі, що здійснюють позитивний і негативний вплив на розвиток банківського сектору. Надано характеристику найбільш значних чинників, показано їх взаємовплив. Негативно впливають на розвиток банківського сектору такі чинники, як небезпечний рівень конкурентної інтерналізації через присутність іноземних банків на українському ринку банківських послуг, високий рівень доларизації кредитів і депозитів, низька якість активів і кредитів та інші. Визначено вплив внутрішніх чинників на розвиток банківського сектору. З використанням динамічного (імітаційного) моделювання на засадах імпульсного процесу доведено, що на розвиток банківського сектору значний вплив здійснює чинник небезпечного рівня конкурентної інтерналізації. Встановлено, що такі стабілізуючі чинники, як зростання попиту на банківські послуги, підвищення довіри до банківської системи та стабілізація курсу національної валюти разом компенсують дестабілізуючий вплив будь-якого негативного фактору, в тому числі щодо конкурентної інтерналізації. Формування позитивних внутрішніх чинників сприятиме прогресивній траєкторії розвитку банківського сектору, зокрема банків з вітчизняним капіталом. В статье обобщены результаты исследования актуального вопроса по эффективному развитию банковского сектора с акцентом на банки с отечественным капиталом, обоснован современный подход к формированию траектории такого развития.
Систематизированы факторы, влияющие на развитие банковского сектора. Факторы распределены на внешние и внутренние. В группе внешних факторов выделены наднациональный и национальный уровни. Факторы наднационального уровня связаны с глобализацией и интеграцией. Прежде всего, это кризисные явления в мировой экономике и финансовой системе, либерализация движения капиталов. Внешние факторы на национальном уровне преимущественно негативно влияют на развитие банковского сектора. Показано, что определенные внешние факторы национального уровня зависят от наднациональных, а внутренние – от национальных.
Внутренние факторы сгруппированы на позитивно и негативно оказывающие влияние на развитие банковского сектора. Приведена характеристика наиболее значительных факторов, показано их взаимное влияние. Негативно влияют на развитие банковского сектора такие факторы, как опасный уровень конкурентной интернализации из-за присутствия иностранных банков на украинском рынке банковских услуг, высокий уровень долларизации кредитов и депозитов, низкое качество активов и кредитов и другие. Определено влияние внутренних факторов на развитие банковского сектора. С использованием динамического (имитационного) моделирования на основе импульсного процесса доказано, что на развитие банковского сектора значительное воздействие оказывает фактор опасного уровня конкурентной интернализации. Установлено, что такие стабилизирующие факторы, как рост спроса на банковские услуги, повышение доверия к банковской системе и стабилизация курса национальной валюты вместе компенсируют дестабилизирующее влияние любого негативного фактора, в том числе относительно конкурентной интернализации. Формирование позитивных внутренних факторов будет способствовать прогрессивной траектории развития банковского сектора, в частности банков с отечественным капиталом.